KINERJA GURU DI TK NEGERI DI ROKAN HULU (MODEL PENELITIAN DESKRIPTIF) - Wades Pawani; Zulkifli. N Zulkifli. N; HUKMI, S HUKMI, S (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The background of this study could also be attributed problems where the performance of teachers in lesson planning, lesson implementation, evaluation of learning, and teachers in the discipline task performance is not optimal, this study aims to determine the State Kindergarten Teacher Performance in Rokan Hulu. The population in this study is a kindergarten teacher in Rokan Hulu State, which has 21 teachers and this population is less than 100 then the samples in this study were all teachers who teach in kindergarten State in Rokan Hulu, which has 21 people. This type of research is a form of quantitative research by using percentages. Collecting data in the study using the observation sheet. Data analysis using quantitative distributive. It can be seen from the results of the analysis of data in which results of the assessment lesson planning by teachers in kindergarten State in Rokan Hulu shows that most kindergarten teachers received grades 34-35 (33.33%) and 38-39 (33.33%). That is, at most State Kindergarten Teacher in Rokan Hulu in the category of lesson planning and assessment result was the implementation of learning by kindergarten teachers in the State in Rokan Hulu shows that most kindergarten teachers scored 99-102 (23.80%) and 111-114 (23.80%). That is, at most State Kindergarten Teacher in Rokan Hulu is learning implementation in higher categories. And based on the research that has been done can be concluded that: Kindergarten Teacher Performance in the State in Rokan Hulu in the lesson plans are medium category, Kindergarten Teacher Performance in the State in the implementation of learning Rokan was higher category.Keywords: Performance of teachers, Learning Planning, Learning Implementation